Nilai-nilai Pendidikan Karakter pada Tokoh Islam Ali bin Abi Thalib dan Relevansinya terhadap Pembentukan Karakter di Era Kontemporer - Apriyani Apriyani (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Character education is becoming increasingly urgent to be implemented in educational institutions, considering that various kinds of non-educative behaviors have now entered educational institutions. The purpose of this study is to (1) represent the values of character education; (2) represent the values of character education depicted in the Islamic figure Ali Bin Abi Talib; (3) represent the relevance of character education values in the history of Ali Bin Abi Talib in the contemporary era. The type of research uses a qualitative approach, the research method uses literature study. The main focus of the research data source is Ali Bin Abi Talib's biography books. The results of the study concluded that the values of character education in the Islamic figure Ali Bin Abi Talib and its relevance in the contemporary era include religious, responsible, disciplined, generous, simple, brave, and intelligent characters. This research contributes as enrichment material and information regarding the values of character education in the Islamic figure Ali Bin Abi Talib and its relevance in the contemporary era.